Relationship between CTF1 gene expression and prognosis and tumor immune microenvironment in glioma - Hongqing Cai; Shen Tian; Angsi Liu; Guanchao Xie; Hongsheng Zhang; Xiaogang Wu; Jinghai Wan; Sai Li (European Journal of Medical Research)
Abstract Objective This study aimed to evaluate CTF1 expression in glioma, its relationship to patient prognosis and the tumor immune microenvironment, and effects on glioma phenotypes to identify a new therapeutic target for treating glioma precisely. Methods We initially assessed the expression of CTF1, a member of the IL-6 family, in glioma, using bioinformatics tools and publicly available databases. Furthermore, we examined the correlation between CTF1 expression and tumor prognosis, DNA methylation patterns, m6A-related genes, potential biological functions, the immune microenvironment, and genes associated with immune checkpoints. We also explored potential associations with drug sensitivity. To assess the impact on glioma cell proliferation and apoptosis, we employed various assays, including the Cell Counting Kit-8, colony formation assay, and flow cytometry. Results CTF1 gene and protein expression were significantly elevated in glioma tissues, and correlated with malignancy and poor prognosis. CTF1 was an independent prognostic factor and negatively associated with DNA methylation. The involvement of CTF1 in m6A modifications contributed to glioma progression. Enrichment analysis revealed immune response pathways linked with CTF1 in glioma, including natural killer cell cytotoxicity, NOD-like receptor signaling, Toll-like receptor signaling, antigen processing, chemokine signaling, and cytokine receptor interactions. CTF1 expression correlated positively with pathways related to apoptosis, inflammation, proliferation, and epithelial–mesenchymal transition, and PI3K–AKT–mTOR signaling. Additionally, CTF1 expression was positively associated with macrophage, eosinophil, and neutrophil contents and immune checkpoint-related genes, but negatively associated with sensitivity to 14 drugs. In vitro experiments confirmed that CTF1 knockdown inhibited glioma cell proliferation and promoted apoptosis. Conclusion This study identifies CTF1 as a significant independent prognostic factor that is closely associated with the tumor immune microenvironment in glioma. Additionally, reduced expression of CTF1 suppresses the proliferation and induces apoptosis of glioma cells in vitro. Consequently, CTF1 is a potentially promising novel therapeutic target for glioma treatment.